Criminal Liability For Begal Victims Who Conduct Forced Defenses Over Noodweer Exces - Yunia Eka Putri (Indonesian Journal of Law and Economics Review, 2020)
The purpose of this research is to know whether the victims of the begal defending the defence were forced to exceed the limit (noodweer exces) could be held a criminal liability. The research methods used are normative and statute approach by collecting data through primary legal materials such as law and secondary sources of legal materials are previous thesis, books, scientific journals, and other literacy. From this research, it can be concluded that the victims who perform self-defense that exceed the limit are not punished.